IDENTIFICATION OF MICROBES ANTAGONISTIC AGAINST Fusarium oxysporum ISOLATED FROM RHIZOSPHERE ZONE OF WATERMELON - Nara-Kusuma, Anak Agung Ngurah; Ramona, Yan; Proborini, Meitini Wahyuni (Jurnal Biologi Udayana, 2018)
This research was aimed to isolate and identify microbes which antagonistic against Fusarium oxysporum , the causative agent of vascular wilt in watermelon plants. The antagonistic microbes were isolated from soil samples collected from rhizosphere of watermelon farm located at west Sanur village, South Denpasar, Bali.  Isolation of fungi and bacteria were conducted on potato dextrose agar medium (PDA) and nutrient agar medium (NA), respectively.  Fungal isolates were then observed under light microscope for its morphological characteristics before identification using a reference book.  Bacterial isolates were characterized using various tests, such as gram stain reaction, existence of endospores, catalase reaction, and ability to ferment various sugars.  Their characteristics were then compared with those described in a reference book.  Two fungal species ( Trichoderma harzianum and Trichoderma viride ) and two bacterial antagonists ( Pseudomonas sp. and Bacillus sp.) were found to have potential to be developed as biocontrol agents to inhibit the growth of F. oxysporum .